A complex of interactions in rare-earth based quantum honeycomb magnets - Treglia, Andrew, author; Gelfand, Martin, advisor; Neilson, James, advisor; Chen, Hua, committee member; Prieto, Amy, committee member (Colorado State University. Libraries, 2025)
Quantum spin liquids (QSLs) represent an exotic state of matter characterized by long-range quantum entanglement and fractionalized excitations. Although predicted theoretically by models such as the Kitaev honeycomb model, experimentally verifying these states in real materials remains a significant challenge in condensed matter physics. This dissertation investigates the magnetic interactions in rare-earth honeycomb materials as potential candidates for realizing QSLs, with a focus on the exchange mechanisms governing their magnetic properties. Through a combination of magnetization, heat capacity, and inelastic neutron scattering experiments, this work systematically explores the magnetic phase behavior of Yb2Si2O7 and ErCl3, two rare-earth compounds with effective spin-1/2 degrees of freedom on geometrically frustrated lattices. The first part of this dissertation examines Yb2Si2O7, which exhibits field-induced quantum phase transitions. Magnetization measurements reveal strong anisotropy consistent with spin-orbit coupled physics, while neutron diffraction and inelastic spectroscopy provide insight into the formation of a Bose-Einstein condensate (BEC) of triplons. However, the absence of staggered magnetization in field-dependent neutron scattering data challenges prior theoretical models and suggests a more complex underlying exchange mechanism. The second part of this work focuses on ErCl3, a material whose honeycomb lattice structure and strong single-ion anisotropy make it a promising candidate for realizing bond-dependent exchange interactions. Single-crystal neutron scattering experiments, performed in a controlled air-free environment, reveal deviations from conventional isotropic exchange, indicating the presence of anisotropic interactions. A systematic analysis of spin wave excitations enables the extraction of exchange parameters, offering experimental constraints for theoretical models describing Kitaev-like interactions in this system. By integrating experimental results with theoretical models, this dissertation advances the understanding of rare-earth-based quantum magnets. The findings underscore the importance of strong spin-orbit coupling and crystal field effects in stabilizing anisotropic exchange, while highlighting key challenges in the experimental verification of QSL behavior. These results provide critical insights for the ongoing search for materials that host quantum spin liquid states and topological excitations, paving the way for future investigations into the realization of quantum matter in real materials.
Keywords: neutron scattering; quantum spin liquids; thermodynamic; quantum magnetism; frustrated magnets; single crystals